Product Inventory Optimization with EOQ Approach in the context of Circular Economy - Prameswari, Balqies Gabriella; Rahman, Aini; Muharam, Harjum; Tjahjana, Redemtus Heru (Research Horizon, 2024)
This research discusses product inventory optimization by applying the Economic Order Quantity (EOQ) approach in the context of circular economy. Circular economy is an economic model that aims to minimize waste and maximize the use of resources with the concept of make-use-return, which is based on the reuse of existing products and materials. In this context, EOQ is used as a tool to optimize product order quantities using the circularity index. The objective of this study is to determine the optimal inventory level that not only reduces wastage and waste, but also takes into account the positive environmental and economic impacts. In this study, the decision variables considered are product order quantity and circularity level. Data is taken from Toko Papa Singkong as a case study to test this model. The results of the analysis show that the application of EOQ in the context of a circular economy can result in a more efficient and sustainable inventory strategy. The practical implication of this research is to provide guidance for companies in managing their inventory better, while taking into account the principles of the circular economy. In conclusion, this research provides an important contribution in the development of a sustainable inventory strategy in the era of circular economy.